Self-Education Into Maturity in Light of the Theoretical Approach of Zdzisław Chlewiński - Weronika Juroszek; Mariola Teresa Kozubek (Vasyl Stefanyk Precarpathian National University, 2023)
This paper aims to answer the research question: How to educate oneself towards maturity in light of the theoretical approach of Zdzisław Chlewiński? Chlewiński developed the theory of mature personality, identifying three components: reliable insight into oneself (authenticity), autonomy and a personalistic attitude towards other people. In this paper, self-education towards maturity is considered as developing the qualities listed by Chlewiński, thus becoming increasingly authentic and autonomous as well as increasingly human in one's relation to the other. Using Chlewiński's method of text analysis, the following areas (tasks) of self-education towards maturity were identified: (1) in terms of honest insight into oneself (authenticity): distancing oneself from the excessive, inflexible use of defence mechanisms that lead to the formation of a distorted self-image and playing inaccurate roles; a reliable answer to the question about the most important life values; the formation of an attitude of gratitude; (2) in terms of autonomy: the formation of pro-social and altruistic life plans; the development of a solid willpower and self-reliance; (3) in terms of the personalistic attitude towards other people: building empathic and supportive relations, distancing oneself from manipulative behaviour (including ingratiation). To illustrate self-education with respect to the aforementioned areas, the selected aspects of biographies of truly mature individuals, prominent Polish people representing different lifestyles, were referred to: Karol Wojtyła, who later became Pope John Paul II; General Fieldorf "Nil" - a hero of World War II; and Wanda Półtawska - a doctor of psychiatry, 102 years old in 2023 when this paper is being written. Their biographies provide inspiration for self-education towards maturity. On the basis of the analysis undertaken, it was concluded that Zdzisław Chlewiński's theory can serve as a source of guidance for further analyses of the biographies of truly mature people.